Chapter Libertà fra tardo medioevo e prima età moderna: il mondo germanofono - Maissen, Thomas (Firenze University Press, 2025)
The author broadens the question of the genesis of the republican experiences to a perspective that is not merely Italian. The space investigated is that of the empire between the late Middle Ages and the early modern age, the scene of a clear evolution of the idea of ​​freedom as a privilege towards a modern conception of freedom. The author highlights how the freedom of the German cities of the late Middle Ages did not refer to political participation but to urban autonomy towards the outside world and to the enjoyment of collective privileges (iura et libertates) by the inhabitants, cives and subjects alike time. Instead, it was in the cities of the Swiss confederation, small territorial states led by patricians or guild magistrates, that an emancipation took shape in the early modern age which replaced monarchic privileges with the republican concept of sovereign freedom.